ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PERAWAT DI RUMAH SAKIT IBU DAN ANAK “X” DI BANDUNG - Akira Akira; Devi Jatmika (Psibernetika, 2015)
According to Indonesia population statistic, birth rate is getting increased along the year. Thus, public health area need improvement especially hospitals for mother and child.  Nurses in the hospitals play important role in serving patients, they have to work in morning or night shift. Based on interview to some nurse at “LM” mother and child hospital in Bandungl, they admitted that the number of patients are getting increased and nurses have to over work and helped their colleagues because the lack of human resources. The willingness to act extra role of their job called organization citizenship behavior (OCB). The aim of this research is to find the OCB among nurses in “LM” nurses. A quantitative descriptive research was conducted. Questionnaire was created based organization citizenship behavior theory by Organ (2006). The result revealed OCB of nurses in “LM” hospitals 32.48% were in low level. In details, four dimensions were in low level: altruism (45.30%), sportsmanship (47.01%), civic virtue (47.01%) and conscientiousness (31.62%). Meanwhile, courtesy was in moderate level (49.57%). Job characteristics that different among nurses and quality of workload should be the factor to explore more in OCB future research.Keywords: Organizational Citizenship Behavior, work performance, nurses